SOSIALISASI PENGOLAHAN LIMBAH PLASTIK MENJADI WASTAFEL SEBAGAI SARANA CUCI TANGAN DI PONDOK PESANTREN NURUL IJTIHAD AL-MA’ARIF NU DESA KUTA KABUPATEN LOMBOK TENGAH - Lalu Auliya Akraboe Littaqwa; M. Said Ramdlan; Legis Ocktaviana Saputri (Jurnal Abdi Insani, 2023)
Washing hands is easy to do, the government even invites residents to make their own hand washing stations. Utilization of plastic waste can be done easily and inexpensively. Plastic waste is an inevitable part nowadays, including in the Kuta Mandalika area. There was an increase in waste generation of 2,815 kg/day from 2016-2018 including plastic waste, proving that waste management has not been effective. Efforts to utilize waste into valuable goods need to be taught from an early age to increase awareness of the potential for plastic waste. What is the perspective of students in responding to plastic waste. To socialize the use of plastic waste into valuable goods and the use of clean water. The activity was carried out at the Nurul Ijtihad Al-Ma'arif NU Islamic Boarding School, Kuta Village, Central Lombok Regency, the method of implementing activities was in the form of preparation, implementation and finishing. Preparation in the form of coordination with related parties in preparing socialization activities. Furthermore, the implementation is in the form of making hand washing facilities from plastic waste. Hand washing facilities are designed to be attractive by utilizing plastic waste. Media for hand washing facilities installed the correct way of washing hands according to WHO (World Health Organization). The socialization that was carried out at the Nurul Ijtihad Al Ma'arif Islamic Boarding School, Kuta Village, Central Lombok Regency went smoothly. Prior to the socialization activity, 46% of students and female students knew that plastic waste could be a more valuable item. After the socialization, it increased to 55.67% knowing that plastic waste is a valuable item. As many as 98% of students and female students want to do one of the 4R principles (reuse, reduce, recycle, replace) and the rest don't want to do it. Most of the students understand the potential for valuable plastic waste in the form of a place for washing hands. Limited knowledge, skills, and difficulties in fighting laziness are the reasons students don't want to carry out 4R activities.